Thermal diffusion and thermal radiation on MHD flow of Casson over an exponentially permeable stretching surface with chemical reaction: A numerical solution - B.Saidi Reddy; S.Hari Singh Naik; B. Shankar Goud (Results in Chemistry)
The current flow model is being developed to examine the parameters of heat and mass transfer by diffusion and thermal radiation on MHD Casson fluid flow with an exponentially increasing surface, while accounting for the impact of the chemical reaction. Using similarity analysis, the basic model equations have been converted into nonlinear, dimensionless ordinary differential equations that, with the aid of suitable transformations, describe the flow of the fluid. The MATLAB built-in method bvp4c is used to get an accurate result. A variety of visually pleasing results have been obtained by assigning appropriate values to the flow variables based on the different scenarios mentioned. As the flow parameters vary, the numerical values of the skin friction factor, the Sherwood number, and the Nusselt number may be obtained. The obtained results have been validated by comparison with published studies. The most significant conclusion of this work is that the Soret number increases, resulting in an increase in the concentration of the species. Additionally, an increase in thermal radiation results in a rise in the temperature profile. Several industries can be the recipients of this research. Cooling and lubrication systems, chemical and industrial processes, heat protection, medical applications, the aviation industry, and metal and polymer processing.